2017
DOI: 10.1016/j.epsl.2017.04.008
|View full text |Cite
|
Sign up to set email alerts
|

The implications of gas slug ascent in a stratified magma for acoustic and ground deformation source mechanisms in Strombolian eruptions

Abstract: The interpretation of geophysical measurements at active volcanoes is vital for hazard assessment and for understanding fundamental processes such as magma degassing. For Strombolian activity, interpretations are currently underpinned by first-order fluid dynamic models which give relatively straightforward relationships between geophysical signals and gas and magma flow. However, recent petrological and high-speed video evidence has indicated the importance of rheological stratification within the conduit and… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
10
0

Year Published

2019
2019
2023
2023

Publication Types

Select...
8
1

Relationship

1
8

Authors

Journals

citations
Cited by 13 publications
(10 citation statements)
references
References 32 publications
0
10
0
Order By: Relevance
“…However, the differences in the gas and crystal contents (and, hence, in the viscosity) between the two magma types are not explicitly taken into account in our model. We nevertheless argue that the low viscosity of mafic, gas-rich magma rising from depth favours its rapid upward migration and interaction with denser, degassed magmas residing in the shallow conduit, which can act as a viscous plug promoting resistance to conduit flow 42,43 . .…”
Section: Discussionmentioning
confidence: 86%
“…However, the differences in the gas and crystal contents (and, hence, in the viscosity) between the two magma types are not explicitly taken into account in our model. We nevertheless argue that the low viscosity of mafic, gas-rich magma rising from depth favours its rapid upward migration and interaction with denser, degassed magmas residing in the shallow conduit, which can act as a viscous plug promoting resistance to conduit flow 42,43 . .…”
Section: Discussionmentioning
confidence: 86%
“…Scaled analogue experiments with gas slugs ascending from a low to high viscosity Newtonian liquid have explored the effects of a near-surface viscous transition on slug flow in a cylindrical conduit (Del Bello et al, 2015;Capponi et al, 2016Capponi et al, , 2017. These investigations proposed three geometrical configurations of the slug-cap interactions based on the viscosity of the upper layer (the viscous "cap") and the size of the cap relative to the bubble volume (Figure 1).…”
Section: Introductionmentioning
confidence: 99%
“…Del also studied the influence of a rheological stratification in the conduit, which was representative of most natural cases, and they showed that slugs ascending through an upper viscous plug of degassed fluid exploded more violently as the slugs were pressurized. Capponi et al (2017) explored shear stresses and gas pressure variations as a function of the rheological contrast).…”
Section: Conduit Flow Dynamicsmentioning
confidence: 99%